A model of tourism planning and design: the Euro-Region Galicia-Northern Portugal as a common tourism destination - Xulio Pardellas de Blas; Carmen Padin Fabeiro (European Regional Science Association (ERSA), 2004)
The new configuration of the Euro-region Galicia-Northern Portugal is in need of a debate on the problems regarding its development. Important questions arise, such as the organization and planning of common tourism destinations. In this paper important and valuable scientific literature on this topic and data from a study carried out by the authors for the Eixo Atlántico in 2001 are used to implement some instruments for their application to the Euro-region. The model presented here is a systemic elaboration of the design of the Euro-region as a common tourism destination in which a formal structure of its elements is provided, which will prove useful to managers and planners in their analysis of situations and in decision-making processes. Key words: common destinations, cross-border regions, planning.
Keywords: 330; common destinations; cross-border regions; planning